Blowup of Solution for a Class of Doubly Nonlinear Parabolic Systems - Jun Lu; Qingying Hu; Hongwei Zhang (Journal of Function Spaces)
An initial boundary value problem for a class of doubly parabolic equations is studied. We obtain sufficient conditions for the blowup of solutions under suitable initial data using differential inequalities.